Phytochemical screening and influence of extraction solvents on antioxidant and antimicrobial activities of Asparagus racemosus willd. Root - Sirikhwan Tinrat,; Monnipha sila-asna, (International Journal of Phytomedicine, 2017)
The bioactive components present in the Asparagus racemosus root are known to be responsible for its medicinal properties. However, the solvent extraction for these bioactive components had effect on bioactive activities. The present study was aimed to compare the effect of using different extraction solvents to extract the active components, antioxidant and antimicrobial activities from Asparagus racemosus root. Aqueous (DW and NW) extracts showed the efficiency of Asparagus racemosus root as antioxidant agent and broad spectrum antibacterial agent against both Gram-positive and Gram-negative. 95% Ethanolic extract had the most potential in the Ferric Reducing Antioxidant Power (FRAP) of 14.400±0.001 mg AAE/100g FW. But aqueous (DW and NW) extracts showed the lowest IC50 value of 4.716±0.002 - 4.757±0.001 mg/ml (IC50 ascorbic acid of 3.422±0.001 mg/ml). Moreover, Natural distilled water extract had also the bactericidal effect on P. aeruginasa ATCC 27853 and K. pneumoniae and E. faecalis DMST 4736 at 3-6 h intervals after incubation. These biological activity may be due partly to the presence of various phytochemical compounds; phenolics, flavonoids saponins, steroids, terpenoids and cardiac glycosides. It also suggests that Asparagus racemosus root was a potential candidate in antioxidant and antimicrobial agents. It was useful in applications with modern medicine in the therapy or prevention of disease as well as the adoption in commercial various health products in the future. In addition to the ethanol and water were suitable solvent to extract the substance, natural distilled water was also the alternative solvent for bioactive compounds extraction.